2015
DOI: 10.1111/jch.12614
|View full text |Cite
|
Sign up to set email alerts
|

Independent Determinants of Maternal and Fetal Outcomes in a Sample of Pregnant Outpatients With Normal Blood Pressure, Chronic Hypertension, Gestational Hypertension, and Preeclampsia

Abstract: The aim of this retrospective study was to evaluate the main independent prognostic factors of negative maternal and fetal outcomes in a relatively large sample of pregnant outpatients (N=906) who were normotensive or affected by chronic hypertension, gestational hypertension, or preeclampsia. Among the studied parameters, the ones significantly associated with negative maternal outcomes were a diagnosis of preeclampsia (vs other forms of hypertension or normotension) and higher serum uric acid level, while an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
(49 reference statements)
2
21
1
Order By: Relevance
“…With or without proteinuria, pregnancy outcomes for the PE groups were poor compared with those of the GH group. Several studies have compared pregnancy outcomes in PE and GH . In a retrospective study of 579 patients with HDP (PE 213, GH 145, chronic hypertension [CH] 221), Cicero et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With or without proteinuria, pregnancy outcomes for the PE groups were poor compared with those of the GH group. Several studies have compared pregnancy outcomes in PE and GH . In a retrospective study of 579 patients with HDP (PE 213, GH 145, chronic hypertension [CH] 221), Cicero et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared pregnancy outcomes in PE and GH . In a retrospective study of 579 patients with HDP (PE 213, GH 145, chronic hypertension [CH] 221), Cicero et al . reported that, compared to other forms of hypertension or normotension, adverse maternal outcomes in PE had an OR of 2.0 (95% CI 1.3–3.1) and adverse neonatal outcomes in PE had an OR of 1.9 (95% CI 1.2–2.9), demonstrating that PE has a poorer prognosis for pregnant women and infants than GH or CH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, identification of risk factors for each adverse outcome in preeclampsia could help target prevention and management. Earlier studies in this respect focused on certain kinds of risk factors and adverse outcomes, or investigated only one or two preeclampsia types . A comprehensive risk profile to identify the risk factor and outcome pairs in women with preeclampsia is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in BP in the first trimester of pregnancy, as well as the finding of an increase in BP before pregnancy, require immediate treatment and monitoring . The early management in these patients reduces the rate of complications during pregnancy and could explain the reason why only PE was found to be associated with negative outcome in the study by Cicero and colleagues …”
mentioning
confidence: 98%
“…3 The early management in these patients reduces the rate of complications during pregnancy and could explain the reason why only PE was found to be associated with negative outcome in the study by Cicero and colleagues. 1 PE is the most severe form of hypertension in pregnancy, characterized by proteinuria and edema in the third trimester of pregnancy. Its pathogenesis is still debated and involves different hormonal, inflammatory, and immunologic mechanisms.…”
mentioning
confidence: 99%